Analytical and numerical research based on one modified refined bending theory - Kasimov, A.T.; Yessenbayeva, G.A.; Kasimov, B.A.; Yessenbayeva, G.A.; Khabidolda, O. (Bulletin of the Karaganda University. Mathematics Series, 2022)
In the article, an analytical and numerical study based on one modified refined bending theory is presented. By the finite difference method, a general numerical calculation algorithm is developed. The solution obtained by the proposed method is compared with the results of known solutions, namely, with the solution of the classical theory, the exact solution, the solution in trigonometric series, as well as with experimental data. Comparison of the results obtained by the method given in the article with the solutions determined by other methods shows sufficient accuracy, which indicates the reliability of the proposed method based on one option of the modified refined bending theory. Classical theory is not applicable to such problems under consideration.